WHY WOULD A CONTRACTOR SKIP A WORK? - A GAME-THEORY APPROACH - Rachmad Irwanto (International Journal of Civil Engineering and Infrastructure, 2023)
There is almost always or at least a disorder phase in construction project. This paper elaborates a game theory review of a real case where a contractor decides to skip a work phase willfully. The review discusses the case through zero-sum and non-zero-sum scenarios to observe what possible ways in terms of the best payoffs through Nash equilibria. So far, despite the skipped work, the real project is undergoing well and will likely to catch the deadline. The game theory analysis on the real case project has found that the payoffs are measured through specifically described strategies and to some extents, could provide insights on decision making process during construction phase.